Analysis of Criminal Acts Without Rights or Against the Law to Commit Conspiracy in Buying, Receiving, Being an Intermediary in the Sale and Purchase of Narcotics in Decision No. 315/Pid.Sus / 2025 / PN Sbw - Sahputra, Rilawadi (International Asia Of Law and Money Laundering, 2026)
This study analyzes the application of elements of criminal acts without rights or against the law in conspiracy to buy, receive, and become an intermediary for the sale and purchase of narcotics based on Decision number 315/Pid.Sus / 2025 / PN Sbw. The research method uses normative juridical approach with statute approach and case approach analysis technique to court decision. The results showed that the panel of judges proved all elements of Article 114 paragraph (2) jo. Article 132 paragraph (1) of Law No. 35 of 2009 concerning narcotics systematically, includes elements of